Theosophical elements in Iqbal's Magnum Opus "the reconstruction of religious thought in Islam": a preliminary review - Hassan Mydin, Shaik Abdullah; Abdul Razak, Mohd Abbas; M M Yusoff, Mahathir (IIUM Press, 2022)
Theosophy is a discourse on the divine wisdom of God behind all created things. In this study, the researchers have scrutinised the theosophical elements found in Iqbal's thought process, particularly in his magnum opus "The Reconstruction of Religious Thought in Islam‖. The central themes of his masterpiece revolved around subjects like God, nature, the human ego and civilization. As a mystic, Iqbal has never failed to embed spirituality on issues pertaining to human survival in the modern world. As a Muslim philosopher, Iqbal emphasised a great deal of lofty religious ideals. With regard to the human ego, Iqbal believed that it has its origin in God. As such, it has some godly attributes to a lesser degree than what is possessed by God. Man‘s God-given minuscule attributes like intelligence and creativity are in no way equal to that of God. Man identified as an ego in Iqbal‘s philosophy must recognise the position of God and at the same time, he has to subdue the forces around him in order to actualize the latent potentials that are there in his psyche. This research has revealed the fact that as a thinker, mystical poet and religious reformer, Iqbal‘s ideas were anchored in the divine wisdom of the Qur‘an. In addition, all of Iqbal‘s theosophical ideas have relevance to the demands of the modern world. As a theoretical study, the researchers have adopted the content and textual analysis methods in their effort to interpret the relevant data to this research.